2006
DOI: 10.1037/1099-9809.12.1.134
|View full text |Cite
|
Sign up to set email alerts
|

Asian American families' collectivistic coping strategies in response to 9/11.

Abstract: Our study investigated the use of individualistic and collectivistic coping strategies among Asian American family members of victims of the World Trade Center (WTC) attacks on September 11th, 2001. Interviews were conducted with 11 Asian Americans who had lost a member of their family in the WTC attacks. Using the Discovery-Oriented Research analysis (Mahrer, 1988), results indicated that Asian Americans utilized the following collectivistic coping methods to deal with their losses: individualistic coping, fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
84
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 45 publications
4
84
0
7
Order By: Relevance
“…A number of studies, however, showed that ethnic minority groups such as African, Asian, and Mexican-Americans tended to hold a more external locus of control (Leung 2001;O'Hea et al 2009;Okeke et al 1999;Ramirez 1988) than European Americans. An orientation towards external locus of control seems consistent with fatalistic beliefs that prevail in many Asian cultures (Norenzayan and Lee 2010;Yeh et al 2006) and in Mexican and other cultures with a strong Catholic tradition (McCabe et al 2008). In African-American cultures, having a more external locus of control orientation may be a way to deal with the disadvantages of poverty, unemployment, and racial discrimination (Threlfall et al 2013).…”
Section: Introductionmentioning
confidence: 91%
“…A number of studies, however, showed that ethnic minority groups such as African, Asian, and Mexican-Americans tended to hold a more external locus of control (Leung 2001;O'Hea et al 2009;Okeke et al 1999;Ramirez 1988) than European Americans. An orientation towards external locus of control seems consistent with fatalistic beliefs that prevail in many Asian cultures (Norenzayan and Lee 2010;Yeh et al 2006) and in Mexican and other cultures with a strong Catholic tradition (McCabe et al 2008). In African-American cultures, having a more external locus of control orientation may be a way to deal with the disadvantages of poverty, unemployment, and racial discrimination (Threlfall et al 2013).…”
Section: Introductionmentioning
confidence: 91%
“…A study (Yeh et al 2006) investigated how 11 Asian Americans living in the NYC area, who had lost a family member, were coping with the tragedy. Four of the participants had lost a child, three had lost a sibling, three had lost a spouse, and one had lost a niece.…”
Section: Impact On Families Of September 11mentioning
confidence: 99%
“…Como afirmaram Yeh et al (2006), as necessidades sociais e os valores culturais têm efeito sobre as estratégias de coping a utilizar aquando da gestão de eventos stressantes e traumáticos. Nas culturas ocidentais, expressar pensamentos e sentimentos associados a um evento traumático não só é aceitável, mas também incentivado socialmente, uma vez que as sociedades ocidentais são baseadas em valores individualistas em que são incentivadas a autonomia e individualidade.…”
Section: Introductionunclassified
“…Quando a adversidade ou o trauma ocorrem, espera-se que as vítimas utilizem estratégias de coping que lhes permitam enfrentar o acontecimento de forma individualista (Yeh et al, 2006). Pelo contrário, as culturas coletivistas, como as sociedades orientais, enfatizam a ligação dos seres humanos (Markus e Kitayama, 1991).…”
Section: Introductionunclassified